THE INFLUENCE OF WORK CULTURE AND INCENTIVES ON EMPLOYEE PRODUCTIVITY PRIMEBIZ HOTEL SURABAYA WITH WORK LIFE BALANCE AS A MODERATION VARIABLE - Berlian, Bruce Dame Dhea; Nadlifatin, Reny; Anshori, Mohamad Yusak (FEB Universitas Sam Ratulangi Manado, 2025)
Abstract. Indonesia is a maritime country that has a variety of beautiful natural attractions, so lodging places such as hotels, villas, and so on are growing rapidly because it can indeed be a business field in the tourism area. Not just a place to stop over but this lodging business can also provide jobs for people. Primebiz Hotel Surabaya (PBS) is one of several in the Prime Plaza Hotels and Resorts (PPHR) national network that operates more than 13 hotels throughout Indonesia. In the world of hospitality also has a variety of unique problems in it, including examples such as Human Resources (HR) who work on the hotel premises. So that as a company engaged in the service sector, this is a challenge for Primebiz Hotel Surabaya because the productivity of its employees must be monitored in order to create good service quality for hotel consumers. This study aims to determine the effect of work culture and incentives on employee productivity with work life balance as a moderating variable. Data collection was carried out by a survey in the form of a questionnaire to Primebiz Hotel Surabaya employees as many as 65 respondents. This research is quantitative research using descriptive analysis and SEMPLS data analysis techniques with SmartPLS software to determine the relationship between variables. The results showed that only hypothesis one has a significant positive effect on employee productivity. Meanwhile, the results of hypotheses two to four do not have a significant positive effect on employee productivity.